Antibiotic usage in pediatric respiratory tract infection - NM Yasin; MB Bahari; HIM Ismail (Indonesian Journal of Pharmacy, 2005)
Respiratory tract infections are the worldwide main cause of death in children aging less than 5 years. In developed countries; respiratory tract infections are the leading cause of morbidity, accounted for 20% of medical consultation, 30% of work absenteeism and 75 % of all antibiotic prescription. Upper respiratory tract infections in children, which often associated with viral infection, and in average about 40 – 60 % of children with upper respiratory tract infections were prescribed with antibiotics. The type of antibiotics also varies from hospital to another.The objectives of this study are to describe the pattern, outcome, and cost of antibiotic usage in pediatric respiratory tract infections. A prospective study of pediatrics admitted to Pediatric Ward, Penang Hospital for respiratory tract infections was carried out. Appropriate descriptive analysiswas used. The results showed that penicillin, erythromycin; amoxicillinclavulanate were the most commonly prescribed antibiotics for respiratory tract infections. The average duration of antibiotic therapy 3.0 ± 3.2 days, fever clearance time 2.2 ± 2.4 days, improvement of sign and symptoms 3.7 ± 2.5 days and mean length of stay in the ward was 4.9 ± 2.8 days. The average cost of antibiotics was RM 14.83 ± 83.13, and total cost of respiratory tract infections treatment was RM 98.88 ± 65.87.Key words: antibiotic, respiratory tract infection, pediatric, hospital